Loss of contrast sensitivity in diabetic patients with LOCS II classified cataracts. Issue 1 (January 1993) - Chylack, L T; Padhye, N; Khu, P M; Wehner, C; Wolfe, J; McCarthy, D; Rosner, B; Friend, J
Abstract : Contrast sensitivity function (CSF) was assessed in a population of diabetics with moderate cataracts to determine if CSF testing provides more information about visual dysfunction than Snellen or Lotmar interferometric visual acuity. With the Lens Opacities Classification Systems Version II (LOCS II) of cataract classification it was possible to grade accurately the type and severity of cataract and nuclear brunescence. The presence of statistically significant relationships between increasing LOCS II classification (worsening cataract) and diminished function, even when the regression model was controlled for Snellen visual acuity, supports the thesis that CSF measurements do provide more information about cataract related visual loss than Snellen acuity alone. Statistically significant (p < or = 0.05) relationships existed between different morphological types of cataract, nuclear colour, and CSF at specific frequencies. The frequencies affected differed with cataract type or nuclear colour, and with distance and near CSF.